Tinjauan Perencanaan Pintu Pengambilan (Intake) Dan Kantong Lumpur Pada Bendung Paku Kabupaten Polewali Mandar - Jenrisari Datu Bakka’; Benyamin Tanan; Herman Welem Tanje (Paulus Civil Engineering Journal, 2022)
There are problems that are often experienced in bends such as problems with sediment transport disorders, flow tapping disorders, problem of eroding until the destruction of building. The pick-up door at Bendung Paku is only able to serve 100 ha, so it takes re-planning the pick-up door to meet the needs of an irrigation area of 466 ha. To reduce the sediment that goes into the irrigation canals are planned mud bags. The study aimed to calculate the dimensions on intake doors and mud bags. The specifications used in this study are the KP-01 and KP-02 Irrigation Planning Standards. In this study, the results of wide openings of intake doors of 1,000 m and a height of 1,670 m. For mud bags with a rinsing time of 7 days can accommodate sediment as much as 254 m3 with a base width dimension of 4,000 m, length of 86 m, flow depth of 0.700. Sediment reservoir depth 0.660 m and downstream depth 0.820 m.